Counterterrorism Strategies in Pakistan: A Critical Analysis of the National Action Plan (NAP) (2014-2018) - Maryam Siddiqa; Lubna Batool; Abida Rafique, (ASIAN Journal of International Peace & Security (AJIPS), 2022)
This research aims to generate an insightful discussion on the National Action Plan approved by the parliament as a Counterterrorism strategy in Pakistan on December 24, 2014. NAP was designed with a purpose to eliminate terrorism and extremism from Pakistan not only by eliminating terrorists and extremists but also their mindsets. Some 20 points were unanimously approved by political parties and civil-military leadership of Pakistan. It was claimed by the state institutions that tangible and productive measures taken under the NAP had reduced violence in the state. However, an in-depth analysis of the NAP (2014-2018) along with its appraisal in the light of the UN Global Counterterrorism Approach concludes that the NAP actually fell short of attaining the conceived objectives of eliminating terrorism from Pakistan. The study concludes that NAP was initiated by the policy makers with a Rational Choice Approach as it was not productive for the common masses rather it largely aimed at attaining and maximizing interests of the few.